Aquaponics as a sustainable and healthy food production system for Portugal - Mata, F. (2022)
The aquaponics biological cycle Aquaponics has enormous potential in the regulation and recycling of valuable nutrients, otherwise lost to the environment with pollution potential. Aquaponics integrates freshwater aquaculture and hydroponics in a mini ecosystem. It uses the water of a Recirculating Aquaculture System (RAS) in soilless plant farming. The process includes a biofilter where nitrifying bacteria oxidize ammonia, resulting from fish excreta or uneaten feed, into nitrates and nitrites. While fish are extremely sensitive to ammonia, they are more tolerant to nitrates and nitrites. Nevertheless, these need also to be removed from the fish environment before accumulation to toxic levels. This is where hydroponics may come in as a useful manner of disposing nitrogen off the RAS. Nitrogen is the main macronutrient for plant growth, therefore an indispensable element in fertilization. The advantages of combining a RAS with hydroponics becomes therefore evident as a win-win solution for the problematic nitrates of the RAS and the expensive nitrogen fertilizers of plant production.